2013
DOI: 10.1111/jen.12042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic changes during laboratory domestication of an olive fly SIT strain

Abstract: Early attempts to apply the SIT on the olive fly, Bactrocera oleae, were unsuccessful, mainly due to the low competitiveness of the sterile mass‐reared males compared with the wild ones. Recently, new efforts are underway in Israel to develop a vigorous and efficient mass‐reared olive fly laboratory strain. To understand the genetics of the adaptation process and possibly link the corresponding loss of competitiveness to genetic markers, we followed the fluctuation of genotypic frequencies of ten microsatellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…On the other hand, results obtained from laboratory colonies must be verified in larger samples of different origin before elevating to species level. As it has been shown by different studies (Gilchrist et al 2012; Parreño et al 2014, Zygouridis et al 2014), lab colonization is accompanied by an adaptation process including severe bottlenecks, hitch-hiking effects and extended inbreeding. This can affect the genetic structure of the populations and, possibly, their symbiotic communities.…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, results obtained from laboratory colonies must be verified in larger samples of different origin before elevating to species level. As it has been shown by different studies (Gilchrist et al 2012; Parreño et al 2014, Zygouridis et al 2014), lab colonization is accompanied by an adaptation process including severe bottlenecks, hitch-hiking effects and extended inbreeding. This can affect the genetic structure of the populations and, possibly, their symbiotic communities.…”
Section: Resultsmentioning
confidence: 84%
“…Generally, competitiveness of the male insects decreases with every generation in the insectary and therefore the mass-reared strains occasionally need to be refreshed by integrating wild genetic material (Gilchrist et al, 2012;Zygouridis et al, 2014). This has been successfully applied in fruit fly programmes (Calkins and Parker, 2005).…”
Section: Sexing Strain Ano Ipcl1mentioning
confidence: 98%
“…However, due to their adaptation to factory, laboratory, and irradiation, flies have significantly reduced fitness (Leftwich et al, 2016). Zygouridis et al (2014) observed a substantial loss of variability between F1 and F2-F5 generations in the laboratory, while in F11 a complete adaptation to the new laboratory environment occurs. It was suggested that loss of variability is responsible for the loss of wild characters like low competitiveness of the sterile mass-reared males compared with the wild ones.…”
Section: Alternative Methods For Protection Against Olive Flymentioning
confidence: 99%
“…Loss of variability was shown with microsatellite markers. Authors suggested a solution to refresh a mass-reared colony with wild material at about every five to eight generations (Zygouridis et al, 2014). Efforts to develop a vigorous and efficient mass-reared laboratory olive fly strain is underway.…”
Section: Alternative Methods For Protection Against Olive Flymentioning
confidence: 99%
See 1 more Smart Citation